Improving photocatalytic performance of ZnO via synergistic effects of Ag nanoparticles and graphene quantum dots1. Issue 28 (28th July 2015) - Wang, Jun; Li, Yan; Ge, Juan; Zhang, Bo-Ping; Wan, Wan
<x xml:space="preserve">Abstract</x> A Ag–graphene quantum dots (GQDs)–ZnO ternary photocatalyst was prepared using GQDs as both a reducing agent and a cation solvent. Photodegradation performance was improved because of the synergic effect of Ag and GQDs.